Baseline morbidity in 2,990 adult African volunteers recruited to characterize laboratory reference intervals for future HIV vaccine clinical trials. - Stevens, W; Kamali, A; Karita, E; Anzala, O; Sanders, E; Jaoko, W; Kaleebu, P; Mulenga, J; Dally, L; Fast, P; Gilmour, J; Farah, B; et al. (Public Library of Science, 2008)
BACKGROUND: An understanding of the health of potential volunteers in Africa is essential for the safe and efficient conduct of clinical trials, particularly for trials of preventive technologies such as vaccines that enroll healthy individuals. Clinical safety laboratory values used for screening, enrolment and follow-up of African clinical trial volunteers have largely been based on values derived from industrialized countries in Europe and North America. This report describes baseline morbidity during recruitment for a multi-center, African laboratory reference intervals study. METHODS: Asymptomatic persons, aged 18-60 years, were invited to participate in a cross-sectional study at seven sites (Kigali, Rwanda; Masaka and Entebbe, Uganda; Kangemi, Kenyatta National Hospital and Kilifi, Kenya; and Lusaka, Zambia). Gender equivalency was by design. Individuals who were acutely ill, pregnant, menstruating, or had significant clinical findings were not enrolled. Each volunteer provided blood for hematology, immunology, and biochemistry parameters and urine for urinalysis. Enrolled volunteers were excluded if found to be positive for HIV, syphilis or Hepatitis B and C. Laboratory assays were conducted under Good Clinical Laboratory Practices (GCLP). RESULTS AND CONCLUSIONS: Of the 2990 volunteers who were screened, 2387 (80%) were enrolled, and 2107 (71%) were included in the analysis (52% men, 48% women). Major reasons for screening out volunteers included abnormal findings on physical examination (228/603, 38%), significant medical history (76, 13%) and inability to complete the informed consent process (73, 13%). Once enrolled, principle reasons for exclusion from analysis included detection of Hepatitis B surface antigen (106/280, 38%) and antibodies against Hepatitis C (95, 34%). This is the first large scale, multi-site study conducted to the standards of GCLP to describe African laboratory reference intervals applicable to potential volunteers in clinical trials. Approximately one-third of all potential volunteers screened were not eligible for analysis; the majority were excluded for medical reasons.